2017
DOI: 10.1513/annalsats.201612-1009as
|View full text |Cite
|
Sign up to set email alerts
|

Critical Thinking in Critical Care: Five Strategies to Improve Teaching and Learning in the Intensive Care Unit

Abstract: Critical thinking, the capacity to be deliberate about thinking, is increasingly the focus of undergraduate medical education, but is not commonly addressed in graduate medical education. Without critical thinking, physicians, and particularly residents, are prone to cognitive errors, which can lead to diagnostic errors, especially in a high-stakes environment such as the intensive care unit. Although challenging, critical thinking skills can be taught. At this time, there is a paucity of data to support an ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 31 publications
(39 reference statements)
0
36
0
2
Order By: Relevance
“…Efficient coordination of care led to appropriate therapeutic intervention and complete diagnostic evaluation. While Type 2 thinking played a pivotal role in this case, many agree that improvement in both type 1 and type 2 critical thinking patterns is one of the most effective strategies in reducing diagnostic errors [ 17 , 18 ]. Physicians must acknowledge that metacognition, or thinking about thinking, is required to not only recognize cognitive biases to prevent anchoring prematurely to a diagnosis but also to expose and subsequently fill knowledge gaps to deliver optimal patient care and achieve better outcomes [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Efficient coordination of care led to appropriate therapeutic intervention and complete diagnostic evaluation. While Type 2 thinking played a pivotal role in this case, many agree that improvement in both type 1 and type 2 critical thinking patterns is one of the most effective strategies in reducing diagnostic errors [ 17 , 18 ]. Physicians must acknowledge that metacognition, or thinking about thinking, is required to not only recognize cognitive biases to prevent anchoring prematurely to a diagnosis but also to expose and subsequently fill knowledge gaps to deliver optimal patient care and achieve better outcomes [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Critical thinking refers to the flexible use of existing knowledge and experience, based on problem analysis and induction reasoning and, ultimately, arriving at a reasonable judgment and a correct choice. 31 Critical thinking, as a basis for clinical decision-making, is directly related to the quality of clinical care services. Studies have shown that nurses' self-esteem is significantly and positively related to critical thinking.…”
Section: Self-esteem Is Positively Correlated With Critical Thinkingmentioning
confidence: 99%
“…However, the classroom teaching format has limitations in that it does not train the audience to integrate cognitive and procedural tasks under time constraints [5]. Furthermore, imparting knowledge of complex critical care topics to junior residents without adequate exposure to direct patient care may hinder their ability to properly absorb the information [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%